87 What factors ultimately influence the place of death of care home residents? A qualitative study of the interaction between care homes and general practitioners in the south wales valleys. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Jones, Ian; Harris, Dylan
Abstract : Background: In Wales, over 50% of care home patients at end of life die in hospital. Initiatives such as advance care planning aim to reduce hospital admissions from care homes at end of life, but improvements have been slow. This study explores why some care home patients are admitted to hospital at end of life, and why similar patients are looked after in their care homes. Methods: The study is a retrospective, thematic analysis of interviews with General Practitioners (GPs) and care home staff. The interviews were based on care home deaths occurring in 6 GP surgeries, 6 nursing homes and 6 residential homes in the South Wales valleys between 01/09/2016 and 31/08/2017. Results: Fifty-seven hospital deaths were discussed, along with a similar number of care home deaths. Overall, 78% of patients overall died an expected death in their care homes. Main themes around hospital admissions were emergency ambulance requests by care homes (33%), arranged admissions by GPs (21%), and family request (14%). Variation was found in the way care homes and GPs managed frail and declining patients, and residents were sometimes admitted to hospital against the wishes of care home staff and families. Other issues identified were difficulties in accessing services, lack of reflection, and conflicting roles. Conclusions: Service provision was fragmented. The author suggests that GPs, Intermediate Care, Ambulance Services, GP Out of Hours, palliative care teams and care homes work together closely to address the issues. Also suggested are regional groups to co-ordinate and monitor end of life care in care homes. National accreditation should be introduced for end of life care in care homes, and regulatory bodies (such as Care Inspectorate Wales) should inspect care homes accordingly. This research fills a gap in our knowledge, and its findings can be applied internationally.